2013
DOI: 10.1007/s10120-013-0235-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of laparoscopy-assisted total gastrectomy in patients with clinical stage I gastric cancer

Abstract: Background Laparoscopy-assisted total gastrectomy (LATG) for gastric cancer is not yet widespread because of the technical difficulty of reconstruction. We have performed LATG on 100 patients with clinical stage I gastric cancer. This study investigated the short-term outcomes of LATG. Methods Between September 2001 and September 2012, 100 patients with clinical stage I gastric cancer underwent LATG with D1 plus beta or D2 lymphadenectomy. Roux-en-Y esophagojejunostomy was performed intracorporeally using end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 22 publications
0
46
1
Order By: Relevance
“…By contrast, one study showed a high incidence of anastomosis-related complications in the LTG group [52]. Pancreatic fistula is another important complication to be considered when performing LTG [20,24]. The incidence of pancreatic fistula did not differ between the LTG and OTG groups.…”
Section: Postoperative Complicationsmentioning
confidence: 93%
See 3 more Smart Citations
“…By contrast, one study showed a high incidence of anastomosis-related complications in the LTG group [52]. Pancreatic fistula is another important complication to be considered when performing LTG [20,24]. The incidence of pancreatic fistula did not differ between the LTG and OTG groups.…”
Section: Postoperative Complicationsmentioning
confidence: 93%
“…It is therefore difficult to assess the course of postoperative recovery in retrospective studies. In most studies, mortality was low and acceptable, with no significant differences between different patient groups [18][19][20][21][22][23][24].…”
Section: Postoperative Recoverymentioning
confidence: 98%
See 2 more Smart Citations
“…The pneumoperitoneum was vulnerable to its placement, and vision was unclear. Therefore, it was not an ideal method and may have resulted in a higher rate of postoperative complications [14,15] , especially in our early experience. Thus, a novel transorally inserted anvil (OrVil; Covidien, Mansfield, MA, United States) was introduced to address the challenge of anvil placement [16] .…”
Section: Discussionmentioning
confidence: 99%